Study on the interaction characteristics between pot seedling and planter based on hanging cup transplanter - Hongbin Bai; Fandi Zeng; Qiang Su; Ji Cui; Xuying Li (Scientific Reports)
Abstract This study aims to investigate the interaction mechanism between the planter and pot seedlings during the operation of a hanging cup transplanter and establish a nonlinear relationship model between the two. The research employs a coupling method of the Discrete Element Method and Multi-Body Dynamics to construct a discrete element model of the cup-type planter and pot seedlings. By setting different planting frequencies (22, 34, and 46 plants/min) as influencing factors, the mechanical variation patterns and collision motion characteristics of the pot seedlings were analyzed. The accuracy of the simulation model was validated using the substrate loss rate after planting as an evaluation metric. Furthermore, based on Artificial Neural Network technology and incorporating BP and GA-BP algorithms, a nonlinear model of the interaction between pot seedlings and the planting device under various parameter conditions was established using simulated field planting test results as the dataset. The research findings indicate that under different planting frequencies, the collision contact points and interaction relationships between the pot seedlings and the planter exhibit significant differences. During the initial collision contact, the collision force reaches its peak, resulting in the most severe pot body damage. Comparative analysis reveals that the GA-BP algorithm demonstrates superior performance in ensuring model accuracy and stability, exhibiting better fitting performance with relative error rates between target and predicted values ranging from 2.25 to 10.54%. The results of this study not only provide important theoretical support for understanding the interaction mechanism between cup-type planter and pot seedlings but also offer valuable practical references for constructing planting quality prediction models in complex field environments.